A Comparison of Speech Outcomes Using Radical Intravelar Veloplasty or Furlow Palatoplasty for the Treatment of Velopharyngeal Insufficiency Associated With Occult Submucous Cleft Palate. Issue 2 (February 2015) - Afrooz, Paul Nader; MacIsaac, Zoe; Rottgers, Stephen Alex; Ford, Matthew; Grunwaldt, Lorelei J.; Kumar, Anand R.
Abstract : Background: The safety, efficacy, and direct comparison of various surgical treatments for velopharyngeal insufficiency (VPI) associated with occult submucous cleft palate (OSMCP) are poorly characterized. The aim of this study was to report and analyze the safety and efficacy of Furlow palatoplasty (FP) versus radical intravelar veloplasty (IVV) for treatment of VPI associated with OSMCP. Methods: A retrospective review of one institution's experience treating VPI associated with OSMCP using IVV (group 1) or FP (group 2) during 24 months was performed. Statistical significance was determined by Wilcoxon matched-pair, Independent-Samples Mann-Whitney U, and analysis of variance (SPSS 20.0.0). Results: In group 1 (IVV), 18 patients were identified from August 2010 to 2011 (12 male and 6 female patients; average age, 5.39 years). Seven patients were syndromic and 11 were nonsyndromic. In group 2 (FP), 17 patients were identified from August 2009 to 2011 (8 male and 9 female patients; average age, 8.37 years). Three patients were syndromic and 14 patients were nonsyndromic. There was statistical significance between the average pretreatment Pittsburgh Weighted Speech Score (PWSS) of the 2 groups (group 1 and 2 averages 19.06 and 11.05, respectively, P = 0.002), but there was no statistical significance postoperatively (group 1 and 2 averages 4.50 and 4.69, respectively, P = 0.405). One patient from each group required secondary speech surgery. Average operative time was greater for FP (140 minutes; range, 93–177 minutes) compared to IVV (95 minutes; range, 58–135 minutes), P < 0.001. Average hospital stay was 3.9 days for IVV (range, 2–9 days) and 3.2 days for FP (range, 2–6 days), with no significant difference ( P = 0.116). There were no postsurgical wound infections, oral-nasal fistulas, postoperative bleeding complications, or mortalities. Conclusions: Nonsyndromic patients with hypernasal speech are treated effectively and safely with either IVV or FP. Intravelar veloplasty trended toward lower speech scores than FP (76% IVV, 58% FP PWSS absolute reduction). Syndromic patients with OSMCP may be more effectively treated with FP (72% IVV vs 79% FP PWSS absolute reduction). Intravelar veloplasty is associated with shorter operative times. Both techniques are associated with low morbidity, improved speech scores, and low reoperative rates.